2021
DOI: 10.1016/s1556-0864(21)01882-7
|View full text |Cite
|
Sign up to set email alerts
|

40P Revealing the association between lung cancer and allergic respiratory diseases: Meta-analysis of cohort studies

Abstract: Gene BM at diagnosis EGFR (n = 53)19 (36%) MET (n = 14) 3 (21%) ALK (n = 12) 4 (33%) ERBB2 (n = 8) 1 (13%) BRAF (n = 7) 3 (43%) ROS (n = 2) 0 (0%) RET (n = 2) 2 (100%)Conclusions: In the analyzed cohort of patients, we note that patients with NSCLC with driver mutations have a high incidence of BM at diagnosis. Contrary to historical controls, these patients with molecular alterations have favorable outcomes despite development of BM. This could be due to the availability of potent active targeted drugs with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies have found that allergy and allergic inflammation are closely related to lung cancer [ 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the detailed mechanisms underlying allergy-promoting lung cancer are still unclear due to the limited experimental investigations that have been conducted.…”
Section: Allergen In Lung Cancermentioning
confidence: 99%
“…Many studies have found that allergy and allergic inflammation are closely related to lung cancer [ 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the detailed mechanisms underlying allergy-promoting lung cancer are still unclear due to the limited experimental investigations that have been conducted.…”
Section: Allergen In Lung Cancermentioning
confidence: 99%